Exploring the efficacy of cyclic vs static aspiration in a cerebral thrombectomy model: an initial proof of concept study. (14th November 2013) - Simon, Scott; Grey, Casey Paul; Massenzo, Trisha; Simpson, David G; Longest, P Worth
Abstract : Background and purpose: Current technology for endovascular thrombectomy in ischemic stroke utilizes static loading and is successful in approximately 85% of cases. Existing technology uses either static suction (applied via a continuous pump or syringe) or flow arrest with a proximal balloon. In this paper we evaluate the potential of cyclic loading in aspiration thrombectomy. Methods: In order to evaluate the efficacy of cyclic aspiration, a model was created using a Penumbra aspiration system, three-way valve and Penumbra 5Max catheter. Synthetic clots were aspirated at different frequencies and using different aspiration mediums. Success or failure of clot removal and time were recorded. All statistical analyses were based on either a one-way or two-way analysis of variance, Holm–Sidak pairwise multiple comparison procedure (α=0.05). Results: Cyclic aspiration outperformed static aspiration in overall clot removal and removal speed (p<0.001). Within cyclic aspiration, Max Hz frequencies (∼6.3 Hz) cleared clots faster than 1 Hz (p<0.001) and 2 Hz (p=0.024). Loading cycle dynamics (specific pressure waveforms) affected speed and overall clearance (p<0.001). Water as the aspiration medium was more effective at clearing clots than air (p=0.019). Conclusions: Cyclic aspiration significantly outperformed static aspiration in speed and overall clearance of synthetic clots in our experimental model. Within cyclic aspiration, efficacy is improved by increasing cycle frequency, utilizing specific pressure cycle waveforms and using water rather than air as the aspiration medium. These findings provide a starting point for altering existing thrombectomy technology or perhaps the development of new technologies with higher recanalization rates.